Direct Imaging of Chiral Domain Walls and Néel‐Type Skyrmionium in Ferrimagnetic Alloys. (16th June 2021) - Seng, Boris; Schönke, Daniel; Yeste, Javier; Reeve, Robert M.; Kerber, Nico; Lacour, Daniel; Bello, Jean‐Loïs; Bergeard, Nicolas; Kammerbauer, Fabian; Bhukta, Mona; Ferté, Tom; Boeglin, Christine; et al.
Abstract: The evolution of chiral spin structures is studied in ferrimagnetic Ta/Ir/Fe/GdFeCo/Pt multilayers as a function of temperature using scanning electron microscopy with polarization analysis (SEMPA). The GdFeCo ferrimagnet exhibits pure right‐handed Néel‐type domain wall (DW) spin textures over a large temperature range. This indicates the presence of a negative Dzyaloshinskii–Moriya interaction that can originate from both the top Fe/Pt and the Co/Pt interfaces. From measurements of the DW width, as well as complementary magnetic characterization, the exchange stiffness as a function of temperature is ascertained. The exchange stiffness is surprisingly more or less constant, which is explained by theoretical predictions. Beyond single skyrmions, it is identified by direct imaging a pure Néel‐type skyrmionium, which due to the expected vanishing skyrmion Hall angle, is a promising topological spin structure to enable applications by next generation of spintronic devices. Abstract : The evolution of chiral spin states is studied in ferrimagnetic Ta/Ir/Fe/GdFeCo/Pt as a function of the temperature using scanning electron microscopy with polarization analysis. The GdFeCo ferrimagnet exhibits pure right‐handed Néel‐type domain walls over a large temperature range with the exchange stiffness deduced from the wall width. Beyond single skyrmions, additionally a pure Néel‐type skyrmionium is found.